Exploring the interaction of firm-level change and national institutional environments in shaping employment and union relations: a comparative case study of four European airlines. Issue 2 (19th January 2019) - Becker-Ritterspach, Florian; Saka-Helmhout, Ayse; Lange, Knut; Geppert, Mike
Abstract: Drawing on the example of the airline industry, this paper explores in a longitudinal comparative case study the question of how firm-level changes and national institutional environments interact in shaping employee and union relations. Adding to previous research in comparative institutional analysis and comparative employment relations, we illustrate that the way in which industry pressures and national-level effects play out to influence employee and union relations depends on firm-level changes, mainly in the form of firm growth, acquisitions and the foundation of new subsidiaries. We show in particular that depending on firm-level changes, the very same firm might engage differently with a given institutional context at different points in time. Hence, our work illustrates the importance of firm growth, acquisitions and the foundation of new subsidiaries in explaining the shifting interaction between the firm and its institutional environment, and its implications for changing employee and union relations within firms.